Estudo dos aspectos de dimensionamento de elementos estruturais de concreto reforçado com fibras com base na teoria de flexão em vigas - Lima, Iva Emanuelly Pereira (2020)
The fibers reinforced concretes (FRC) has less crack propagation and, consequently, promotes an increase in tenacity and residual strength for the composite. In spite of this, the increase in this capacity only happens if the concrete is dosed and applied properly and, for this, there are reference codes that establish aspects of technological control and sizing for the use of the FRC. However, in these documents, with respect to one of the sizing aspects, the resulting resistant strength portion of the fibers is described for some specific applications, where it is considered that the maximum load corresponds to the crack load, which may not apply to concretes that have a preferential fiber orientation. In view of this, knowing the significant change that the orientation of the fibers can provide, and in order to determine the resulting resistant strength of the fibers in the tensioned part of a fluid fibrous concrete, a study related to the proposal of a model for calculating the FRC based on that definition. The establishment of this model was obtained based on the theory of bending in beams, from the three-point bending test standardized by EN 14651 (2007), where a sample of reinforced concrete with steel fibers (SFRC) and another sample were used produced with polymeric fibers (PFRC). According to the study, it was found that the maximum load value did not correspond to the crack load value for any beam under analysis and, in general, it was noticed that the loads are statistically different from each other. Based on this difference, the positioning of the neutral line of the structure was analytically defined and, from equilibrium equations, a calculation model was determined for the resulting resistant strength of the fibers in the tensioned part of the concrete. From this, the values obtained through the proposed model were compared with the results determined in accordance with the FIB Model Code 2010 (2013) and according to ACI 544.8R (2016), where it was found that the results showed variations. In order to investigate these dispersions, an analysis of the sensitivity parameters of the equations was made and it is concluded that the proposed calculation model does not present any parameter of influence in the analyzed context, which showed that the analytical equation developed in this work can be preliminarily validated for the sizing of FRC structural elements.